Prevalence of the main mental disorders during the COVID-19 pandemic. - Mejía-Zambrano, Henry (2022)
Objective: To determine the prevalence of the main mental disorders in health workers and the general population, in the context of the coronavirus 19 (COVID-19) pandemic. Material and Methods: The article follows the norms of the PRISM Guide for systematic revisions. A bibliographical search was made in Pub Med /MEDLINE from March 2020 until the 24 of March of 2021, the search strategies being duly evaluated by means of the Cochrane Manual of systematic reviews; similarly, the Mendeley program was used to qualify bibliographical references and eliminate duplicated articles. Results: Twenty-two studies were included in the analysis with a total average of 24 593 participants. In the general population, anxiety had a prevalence of 36.4%; depression, 26.6%; stress, 44.2% and post-traumatic stress disorder (PTSD), 5.9%. Women presented more frequently symptoms of anxiety and depression, whereas the majority of men manifested symptoms of stress. Among the health professionals, stress and sleep disturbances were the main problems, both with a prevalence of 43%. Conclusion: The mental health of frontline health professionals and workers, as well as the general population’s is seriously compromised in the COVID-19 pandemic, with anxiety, depression, stress, insomnia and PTSD as the most prevalent conditions.